A new species of Kerkia Radoman, 1978 (Caenogastropoda, Hydrobiidae) from Bosnia and Herzegovina - Hofman, Sebastian (Zookeys, 2020)
A new species of Kerkia, K. briani Rysiewska & Osikowski, sp. nov. is described from the spring Polički Studenac Vrelo (Crkvina), adjacent to the Trebišnjica River (Bosnia and Herzegovina) collected with Bou-Rouch technique, pumped from an interstitial habitat 50 cm below the bottom of the spring. The shell, female reproductive organs, and the penis are described and illustrated. Mitochondrial cytochrome oxidase subunit I (COI) and nuclear histone H3 partial sequences confirm the distinctness of the new species, and molecularly based phylogenetic relationships of Kerkia are briefly presented.